Success Factors for Implementing Robotic Process Automation (RPA) in Accounting Information Systems within the Trade Sector: a Systematic Literature Review - Dony Waluya Firdaus; Ridwan Zulkifli; Muhamad Nawawi; Irawan Afrianto; Estiko Rijanto; Irfan Sumitra (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2025)
Digital transformation requires more operational efficiency in the trade sector, with RPA turning out to be one of the key technologies for modernizing Accounting Information Systems. This paper seeks to identify the adoption patterns and dominant factors determining the success of RPA implementation in finance and accounting functions within the trade sector-a domain which, so far, has been underexplored as compared to the banking sector. By means of a Systematic Literature Review with PRISMA 2020 guidelines, along with the bibliometric analysis of 72 Scopus-indexed articles published between 2020 and 2025, this study maps the evolution in technology adoption. The study portrays that RPA's adoption has moved beyond the automation of mere back-office repetitive tasks, such as reconciliation and data entry, toward the orchestration of end-to-end trade processes spanning procurement and logistics, while integrating with AI for handling unstructured data. The study further finds evidence that successful implementation relies on a maturity path leading from accurate selection of routine and high-volume processes to standardization of data input. The sustainability of RPA advantages is defined by organizational capabilities through CoE and successful change management, while supported by strategic governance through alignment of business objectives with information technology.   The result of this study provides a theoretical framework and practical guidance for trading firms in ensuring investments in RPA result in performance metrics and increased compliance.